EFFECT OF NUMBER OF APLLICATION AND LEVELS OF SEAWEED (SEA FORCE 1) ON THE FLOWERING AND FRUITY GROWTH OF TWO SQUASH CULTIVARS Cucurbita pepo L. - Abdulraheem S. Mohammed (Mesopotamia Journal of Agriculture)
This study was Conducted in the vegetable farm research , College of agriculture , Duhok university Three levels of Seaweed extract : Sea Force 1 (i،e zero, 2, 3ml /L) as a foliar application in two squash Cultivars: “Mullah Ahmed “ and “ Zucchini “ at Spring and autumn growing season / 2009 had been used. Plants were sprayed once ، at the beginning of flowering and twice (at the beginning of flowering and the second after, 15 days from the first spraying). Results indicated that Sea Force 1 twice caused a significant increase in the number of pistillite flower which reached 13.36 , 13.33 at the two seasons respectively, while no significant effects on the number of staminate flowers at the two growing season. We concluded that spraying with Sea Force1 twice at 3ml/L gave the best results .